Normal-temperature surface-modified flexible oxide solid electrolyte and preparation method and application thereof

By modifying the surface of oxide ceramic powder, flexible oxide solid electrolyte with self-healing ability is prepared, which solves the problems of low conductivity and short cycle life of existing solid electrolytes, and achieves the effects of high conductivity and wide temperature tolerance range, providing strong support for the development of all-solid lithium metal batteries.

CN119601756APending Publication Date: 2025-03-11BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411685648.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When used at room temperature, the conductivity of existing solid electrolytes is low, resulting in lithium-ion batteries operating at higher temperatures or having electrode interface contact problems, short cycle life, and unable to meet the requirements of large-scale production applications.

Method used

By designing a polymer with self-healing ability and modifying the surface of the oxide ceramic powder, the interface compatibility and dispersion are significantly improved, a flexible oxide solid electrolyte with weak interaction coupling was prepared.

Benefits of technology

It achieves high conductivity, wide temperature tolerance range and high structural stability, and improves the ionic conductivity, safety and cycling performance of all-solid lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601756A_ABST
    Figure CN119601756A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid electrolyte, in particular to normal-temperature surface modified flexible oxide solid electrolyte and a preparation method and application thereof. The normal-temperature surface-modified flexible oxide solid electrolyte is prepared from the following raw materials: a monomer, polyethylene oxide, a solvent, an initiator, a modified oxide ceramic electrolyte and electrolyte salt, wherein the mass of the monomer is 1-10% of the total mass of the components; the molar ratio of the initiator to the monomer is 0.01%-0.1%; the molar ratio of the electrolyte salt to the monomer is 1: (6-12); the mass ratio of the electrolyte salt to the modified oxide ceramic electrolyte is 1: (2.5-5). The flexible oxide solid electrolyte has high conductivity, wide temperature tolerance range and high structural stability, and when the flexible oxide solid electrolyte is applied to an all-solid-state lithium metal battery, the ionic conductivity, safety and cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid electrolyte technology, and in particular to a room-temperature surface-modified flexible oxide solid electrolyte and a preparation method and application thereof. Background Art

[0002] The rapid development of portable electrochemical devices today has put forward higher and higher requirements for energy batteries. Lithium-ion batteries are widely used as power sources for various electronic devices due to their high energy density and operating voltage, low cost, long cycle life and basically no pollution to the environment. At present, liquid electrolytes have become the choice of most commercial lithium-ion batteries due to their high ionic conductivity, but there are also many problems, such as insufficient safety, poor sealing, limited operating temperature range, easy to be corroded, insufficient mechanical stability, etc. Therefore, it is necessary to study a new type of electrolyte to replace liquid electrolytes. The emerging solid electrolytes are considered to be ideal materials for electrochemical applications due to their high safety, non-flammability, chemical and electrochemical stability, and easy adjustment of shape and structure. In recent years, they have received widespread attention from all over the world and have developed rapidly.

[0003] The solid electrolytes currently studied are mainly divided into inorganic ceramic electrolytes and polymer solid electrolytes. 0.67-x Li 3x TiO3 oxide and Li 1+x Al x Ge 2-x (PO4)3 phosphate solid electrolyte has good electrochemical performance and environmental stability, and its preparation method is simple, but its hard texture and prominent electrode / electrolyte interface problems limit its industrial development. Polymer electrolytes are composed of polymer matrices (such as polyesters, polyethers, and polyamines) and lithium salts (such as LiClO4, LiPF6, LiTFSI, etc.). Polymer electrolytes have great potential in realizing large-scale applications of flexible all-solid-state lithium batteries due to their excellent solid-state electrochemical properties such as light weight, flexibility, easy processing, and low price. However, the limited movement of polymer crystal segments leads to very low ionic conductivity (<10 at room temperature). –6 Scm -1 ), and the lower mechanical strength is not enough to suppress the generation of lithium dendrites.

[0004] High ionic conductivity, low ionic area specific resistance, high electronic area specific resistance, high ion selectivity, wide electrochemical stability window, good chemical compatibility, excellent thermal stability, excellent mechanical properties, simple manufacturing process, and environmental friendliness are the main characteristics of good solid electrolytes. However, it is difficult for a single type of SSE to fully meet the above challenging requirements. Therefore, composite solid electrolytes with the performance of both ceramic electrolytes and polymer electrolytes have received more attention. By adjusting the surface groups of ceramic electrolytes, the structure of polymer electrolytes, and the ratio of the two, a large number of composite solid electrolytes with excellent performance have been prepared.

[0005] At the same time, oxide ceramic electrolytes are difficult to prepare. After the material is synthesized, high temperature and high pressure processing are still required during use, which brings huge energy consumption to the preparation process. At the same time, since flexible oxide solid electrolytes have higher boundary ion conductivity, processing and ductility, and interface compatibility, they are conducive to the industrialization and practical application of all-solid-state batteries. When existing solid electrolytes are used in lithium-ion batteries, they can only operate at higher temperatures due to their low conductivity, or there are interface contact problems between the positive and negative electrodes, resulting in a generally short cycle life and unable to meet the requirements of large-scale production applications. Therefore, it is of great significance to develop a preparation method for room temperature surface-modified flexible oxide solid electrolytes for composite solid electrolytes. Summary of the invention

[0006] The purpose of this application is to provide a room temperature surface modified flexible oxide solid electrolyte and its preparation method and application in view of the shortcomings of the current technology. This application is to design a polymer containing self-repair and self-healing ability, and to modify the surface of oxide ceramic powder to significantly improve the interfacial compatibility and dispersibility of high oxide ceramic powder, thereby obtaining a flexible oxide solid electrolyte with weak interaction coupling. It has achieved innovation in technology and improved the comprehensive performance of solid electrolytes. The flexible oxide solid electrolyte of this application has high conductivity, wide temperature tolerance range, high structural stability, and has broad application prospects in the field of polymer composite electrolytes. It is used in all-solid-state lithium metal batteries to improve the ionic conductivity, safety and cycle performance of the battery.

[0007] In the first aspect, the present application provides a room temperature surface modified flexible oxide solid electrolyte, which adopts the following technical solution: A room-temperature surface-modified flexible oxide solid electrolyte comprises the following preparation raw materials: a monomer, polyethylene oxide, a solvent, an initiator, a modified oxide ceramic electrolyte and an electrolyte salt, wherein the mass of the monomer is 1%-10% of the total mass of each component; the molar ratio of the initiator to the monomer is 0.01%-0.1%; the molar ratio of the electrolyte salt to the monomer is 1:6-12; the mass ratio of the electrolyte salt to the modified oxide ceramic electrolyte is 1:2.5-5; the mass ratio of the polyethylene oxide to the modified oxide ceramic electrolyte is 2:5; and the electrolyte salt is a lithium salt.

[0008] By adopting the above technical scheme, the flexible oxide solid electrolyte of the present application is designed to contain a polymer with self-repair and self-healing ability, and by modifying the surface of the oxide ceramic powder, the interfacial compatibility and dispersibility of the high oxide ceramic powder are significantly improved, thereby obtaining a flexible oxide solid electrolyte with weak interaction coupling. This electrolyte has achieved technical innovation and improved the comprehensive performance of the solid electrolyte. Monomer: As the basic unit of the polymerization reaction, it undergoes polymerization reaction with the initiator to form a polymer matrix. The selection and content of the monomer have an important influence on the performance of the electrolyte. Polyethylene oxide: As part of the polymer matrix, it has good flexibility and ductility, which helps to improve the overall mechanical properties of the electrolyte. Solvent: Used to dissolve monomers, initiators and other additives so that they can be fully mixed and participate in the polymerization reaction. Initiator: Polymerizes with the monomer to form a polymer chain. The selection and molar ratio of the initiator have an important influence on the structure and properties of the polymer. Modified oxide ceramic electrolyte: The surface of the lithium lanthanum zirconium tantalum oxide powder is grafted and modified by allyltriethoxysilane, which significantly improves the interfacial compatibility and dispersibility of the lithium lanthanum zirconium tantalum oxide powder. This improved compatibility helps the lithium lanthanum zirconium tantalum oxide powder to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the flexible oxide solid electrolyte. Electrolyte salt: mixed with the monomer in a certain proportion to participate in the polymerization reaction. The type and content of the electrolyte salt have an important influence on the conductivity and electrochemical stability of the electrolyte. Lithium salt: as the main ion source of the electrolyte, it provides a lithium ion conduction path. The selection and content of lithium salt have an important influence on the ionic conductivity and operating voltage window of the electrolyte. In summary, the flexible oxide solid electrolyte of the present application achieves the characteristics of high conductivity, wide temperature tolerance range, high structural stability, etc. by optimizing the proportion and synergy of each component, providing good application prospects for all-solid-state lithium metal batteries.

[0009] Preferably, the lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium perchlorate.

[0010] Preferably, the modified oxide ceramic electrolyte is a modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

[0011] Preferably, the preparation method of the modified lithium lanthanum zirconium tantalum oxide solid electrolyte is as follows: weigh 0.5 g of lithium lanthanum zirconium tantalum oxide powder with an average particle size of 3-5 μm into a reactor, add 2.0 mL of allyl triethoxysilane, 30 mL of anhydrous ethanol, 80 μL of deionized water, condense and reflux at 70°C for 5 hours, centrifuge, wash with water and alcohol three times each, dry in a forced air drying oven at 60°C for 12 hours, and dry in a vacuum oven at 60°C for 12 hours to obtain a modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

[0012] By adopting the above technical scheme, the surface of lithium lanthanum zirconium tantalum oxide powder is grafted and modified by allyltriethoxysilane, which can significantly improve the interfacial compatibility and dispersibility of lithium lanthanum zirconium tantalum oxide powder. This improved compatibility helps the lithium lanthanum zirconium tantalum oxide powder to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the flexible oxide solid electrolyte. The modified lithium lanthanum zirconium tantalum oxide solid electrolyte has better structural stability and can maintain good morphology and performance at high temperatures, which is beneficial to improving the safety and cycle life of all-solid-state lithium metal batteries. In summary, the modified lithium lanthanum zirconium tantalum oxide solid electrolyte plays a key role in this application. Through the synergistic effect with other raw materials, it significantly improves the comprehensive performance of the flexible oxide solid electrolyte, providing strong support for the development of all-solid-state lithium metal batteries.

[0013] Preferably, the initiator is at least one of azobisisobutyronitrile and potassium persulfate; and the solvent is a mixture of one or more of ethanol, N,N-dimethylformamide, dimethyl sulfoxide and acetonitrile.

[0014] Preferably, the monomer is a mixture of one or more of allyltriethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, vinyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, polyethylene glycol monomethyl ether acrylate, 2-amino-4-hydroxy-6-methylpyrimidine and isocyanoethyl methacrylate.

[0015] In a second aspect, the present application provides a method for preparing a room temperature surface-modified flexible oxide solid electrolyte, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned room temperature surface-modified flexible oxide solid electrolyte, comprising the following steps: S71, mixing the monomer and the solvent, condensing and refluxing at a certain temperature, filtering, washing, and drying after sufficient reaction, to prepare monomer A; S72, uniformly mixing the modified oxide ceramic electrolyte, the initiator, the monomer A, and the solvent, reacting under nitrogen protection, cooling to room temperature, centrifuging the obtained product, washing, and drying to obtain a polymer; and transferring the obtained product to a glove box for storage for later use; S73. After uniformly mixing the polymer, polyethylene oxide, lithium salt and solvent, the mixture is cast into a polytetrafluoroethylene mold to form a film, and the solvent is evaporated to obtain a room temperature surface-modified flexible oxide solid electrolyte.

[0016] Preferably, in step S72, the reaction temperature is 60-80°C, and the drying temperature is 50-80°C.

[0017] In a third aspect, the present application provides an application of a room temperature surface modified flexible oxide solid electrolyte, using the following technical solution: As a general technical concept, the present application also provides the application of the above-mentioned room temperature surface modified flexible oxide solid electrolyte, which is applied to an all-solid-state lithium metal battery. The all-solid-state lithium metal battery is assembled in the order of positive electrode shell, positive electrode, room temperature surface modified flexible oxide solid electrolyte, negative electrode, steel sheet, shrapnel, and negative electrode shell to obtain an all-solid-state lithium metal button battery.

[0018] Preferably, the positive electrode of the all-solid-state lithium metal battery is a positive electrode coated with one of lithium cobalt oxide, ternary materials, lithium iron phosphate, aluminum foil and lithium sheet, and the negative electrode is a lithium sheet.

[0019] In summary, the beneficial technical effects of this application are: 1. Improved interfacial compatibility and dispersibility of oxide ceramic powders: The surface of lithium lanthanum zirconium tantalum oxide powders was grafted with allyl triethoxysilane to significantly improve the interfacial compatibility and dispersibility of lithium lanthanum zirconium tantalum oxide powders. This improved compatibility helps lithium lanthanum zirconium tantalum oxide powders to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the flexible oxide solid electrolyte.

[0020] 2. Improved the comprehensive performance of solid-state electrolytes: The prepared room-temperature surface-modified flexible oxide solid electrolyte has good ductility and flexibility, better interface compatibility, and does not require tablet sintering at high temperatures, so that the solid-state electrolyte has the common advantages of ceramic electrolytes and polymer electrolytes, and the prepared all-solid-state lithium metal battery has good performance.

[0021] 3. Improved conductivity of solid electrolyte: The flexible oxide solid electrolyte obtained in this application has high conductivity, and the room temperature ionic conductivity reaches 1.2×10 -4 S / cm, which is beneficial to improve the ionic conductivity of the battery.

[0022] 4. Expanded the working voltage window of the solid-state electrolyte: The flexible oxide solid-state electrolyte obtained in this application has a high working voltage window, and the decomposition voltage is ≥4.68V, which supports its normal operation in the field of solid-state electrolytes.

[0023] 5. Improved compressive performance of the solid electrolyte: The flexible oxide solid electrolyte obtained in this application has good compressive performance, with a pressure exceeding 5000kg, and no obvious deformation or performance degradation.

[0024] 6. Improved chemical and electrochemical stability of solid electrolytes: The flexible oxide solid electrolyte obtained in this application has good chemical and electrochemical stability, does not corrode metals, and can be composited with metals such as copper and aluminum to prepare complex devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 Schematic diagram of the preparation of the flexible oxide solid electrolyte membrane of Example 1; Figure 2 This is a physical picture of the flexible oxide solid electrolyte membrane of Example 1; Figure 3 This is a structural diagram of the flexible oxide solid electrolyte membrane of Example 1 under a scanning electron microscope; Figure 4 The conductivity curve of the flexible oxide solid electrolyte membrane of Example 1 is changed with temperature; Figure 5 The capacity and charge-discharge efficiency curves of the flexible oxide solid electrolyte membrane of Example 1 for a lithium-ion full battery in a long cycle at a rate of 0.2C; Figure 6 The flexible oxide solid electrolyte membrane of Example 1 is used in a lithium ion symmetrical battery at a current density of 0.1 mAh / cm -2 Overpotential curves of long cycles. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] Preparation Example 1 Preparation of modified lithium lanthanum zirconium tantalum oxide solid electrolyte The preparation method of the modified lithium lanthanum zirconium tantalum oxide solid electrolyte is as follows: weigh 0.5 g of lithium lanthanum zirconium tantalum oxide powder with an average particle size of 4 μm into a reactor, add 2.0 mL of allyltriethoxysilane, 30 mL of anhydrous ethanol, and 80 μL of deionized water, condense and reflux at 70°C for 5 hours, centrifuge, wash with water and alcohol three times each, dry in a forced air drying oven at 60°C for 12 hours, and dry in a vacuum oven at 60°C for 12 hours to obtain a modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

[0028] Example 1 The raw materials for preparing a room-temperature surface-modified flexible oxide solid electrolyte include: 0.5g of modified lithium lanthanum zirconium tantalum oxide solid electrolyte, 1.0g of 2-amino-4-hydroxy-6-methylpyrimidine, 1.32g of isocyanoethyl methacrylate, 2.0mL of polyethylene glycol monomethyl ether acrylate, 5mg of azobisisobutyronitrile, 50mL of anhydrous dimethyl sulfoxide, 20mL of cyclohexane, 0.2g of polyethylene oxide, 0.1g of lithium bis(trifluoromethylsulfonyl)imide, and 5mL of acetonitrile.

[0029] The method for preparing the above-mentioned room-temperature surface-modified flexible oxide solid electrolyte comprises the following steps: The first step: weigh 1.0g of 2-amino-4-hydroxy-6-methylpyrimidine into a reaction bottle, add 30mL of anhydrous dimethyl sulfoxide under nitrogen protection, stir at 150°C for 10min, cool to room temperature, then add 1.32g of isocyanoethyl methacrylate, continue stirring and react for 2h, after the reaction is completed, precipitate in an ice bath, filter to obtain a filter membrane, wash three times with dimethyl sulfoxide and cyclohexane, dry in a blast drying oven at 50°C for 12h, and dry in a vacuum oven at 50°C for 12h to obtain a white solid, i.e., 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)ethyl methacrylate.

[0030] Step 2: Weigh 0.5 g of modified lithium lanthanum zirconium tantalum oxide solid electrolyte into a reaction bottle, add 2.0 mL of polyethylene glycol monomethyl ether acrylate, 0.5 g of ethyl 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)methacrylate, 5 mg of azobisisobutyronitrile, and 20 mL of anhydrous dimethyl sulfoxide, react at 70°C for 24 h under nitrogen protection, cool to room temperature, centrifuge, wash with dimethyl sulfoxide, wash with ethanol three times each, dry in a forced air drying oven at 60°C for 12 h, and dry in a vacuum oven at 60°C for 12 h to obtain about 0.5 g of a white solid.

[0031] Step 3: Weigh 0.5g of the product from the second step into a sample bottle, add 0.2g of polyethylene oxide, 0.1g of lithium bis(trifluoromethylsulfonyl)imide, and 5mL of acetonitrile, and stir for 24h. Apply the obtained uniform solution on the substrate by blade coating, evaporate the solvent, and obtain a white film, i.e., a flexible oxide solid electrolyte membrane.

[0032] Step 4: Assemble lithium-ion button cells in the order of positive electrode shell-positive electrode-flexible oxide solid electrolyte-negative electrode-steel sheet-spring-negative electrode shell. The positive electrode of the lithium iron phosphate|lithium full battery is an aluminum foil coated with lithium iron phosphate, and the negative electrode is a lithium sheet; the positive electrode of the lithium symmetric battery is a lithium sheet, and the negative electrode is a lithium sheet.

[0033] Example 2 A room temperature surface modified flexible oxide solid electrolyte raw material includes: 0.5g modified lithium lanthanum zirconium tantalum oxide solid electrolyte, 1.0g 2-amino-4-hydroxy-6-methylpyrimidine, 1.32g isocyanoethyl methacrylate, 2.0mL polyethylene glycol monomethyl ether acrylate, 5mg azobisisobutyronitrile, 50mL dimethyl sulfoxide, 20mL cyclohexane, 0.2g polyethylene oxide, 0.1g lithium bis(trifluoromethylsulfonyl)imide, and 5mL acetonitrile.

[0034] The method for preparing the above-mentioned room-temperature surface-modified flexible oxide solid electrolyte comprises the following steps: Step 1: Weigh 1.0 g of 2-amino-4-hydroxy-6-methylpyrimidine into a reaction bottle, add 30 mL of dimethyl sulfoxide under nitrogen protection, stir at 150° C. for 10 min, cool to room temperature, then add 1.32 g of isocyanoethyl methacrylate, continue stirring and react for 2 h, after the reaction is completed, precipitate in an ice bath, filter to obtain a filter membrane, wash three times with dimethyl sulfoxide and cyclohexane, dry in a blast drying oven at 50° C. for 12 h, and dry in a vacuum oven at 50° C. for 12 h to obtain a white solid, i.e., 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)ethyl methacrylate.

[0035] Step 2: Weigh 0.5 g of modified lithium lanthanum zirconium tantalum oxide solid electrolyte into a reaction bottle, add 2.0 mL of polyethylene glycol monomethyl ether acrylate, 0.5 g of ethyl 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)methacrylate, 5 mg of azobisisobutyronitrile, and 20 mL of dimethyl sulfoxide, react at 70°C for 24 h under nitrogen protection, cool to room temperature, centrifuge, wash with dimethyl sulfoxide, wash with ethanol three times each, dry in a forced air drying oven at 60°C for 12 h, and dry in a vacuum oven at 60°C for 12 h to obtain about 0.5 g of a white solid.

[0036] Step 3: Weigh 0.5 g of the reaction product from the second step, add 0.2 g of polyethylene oxide, 0.1 g of lithium bis(trifluoromethylsulfonyl)imide, and 5 mL of acetonitrile into a sample bottle, stir for 24 h, and apply the resulting uniform solution on a substrate by a doctor blade coating process. Volatilize the solvent to obtain a white film, i.e., a flexible oxide solid electrolyte membrane.

[0037] Step 4: Assemble lithium-ion button cells in the order of positive electrode shell-positive electrode-flexible oxide solid electrolyte-negative electrode-steel sheet-spring-negative electrode shell. The positive electrode of the lithium iron phosphate|lithium full battery is an aluminum foil coated with lithium iron phosphate, and the negative electrode is a lithium sheet; the positive electrode of the lithium symmetric battery is a lithium sheet, and the negative electrode is a lithium sheet.

[0038] Example 3 A room temperature surface modified flexible oxide solid electrolyte raw material includes: 0.5g modified lithium lanthanum zirconium tantalum oxide solid electrolyte, 1.0g 2-amino-4-hydroxy-6-methylpyrimidine, 1.32g isocyanoethyl methacrylate, 2.0mL polyethylene glycol monomethyl ether acrylate, 5mg azobisisobutyronitrile, 50mL dimethyl sulfoxide, 20mL cyclohexane, 0.2g polyethylene oxide, 0.15g lithium bis(trifluoromethylsulfonyl)imide, and 5mL acetonitrile.

[0039] The method for preparing the above-mentioned room-temperature surface-modified flexible oxide solid electrolyte comprises the following steps: Step 1: Weigh 1.0g of 2-amino-4-hydroxy-6-methylpyrimidine into a reaction bottle, add 30mL of anhydrous dimethyl sulfoxide under nitrogen protection, stir at 150°C for 10min, cool to room temperature, then add 1.32g of isocyanoethyl methacrylate, continue stirring and reacting for 2h, after the reaction is completed, precipitate in an ice bath, filter by suction, obtain a filter membrane, wash three times with dimethyl sulfoxide and cyclohexane, dry in a forced air drying oven at 50°C for 12h, and dry in a vacuum oven at 50°C for 12h. A white solid is obtained, namely ethyl 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)methacrylate.

[0040] Step 2: Weigh 0.5 g of modified lithium lanthanum zirconium tantalum oxide solid electrolyte into a reaction bottle, add 2.0 mL of polyethylene glycol monomethyl ether acrylate, 0.5 g of ethyl 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)methacrylate, 5 mg of azobisisobutyronitrile, and 20 mL of dimethyl sulfoxide, react at 70°C for 24 h under nitrogen protection, cool to room temperature, centrifuge, wash with dimethyl sulfoxide, wash with ethanol three times each, dry in a forced air drying oven at 60°C for 12 h, and dry in a vacuum oven at 60°C for 12 h to obtain about 0.5 g of a white solid.

[0041] Step 3: Weigh 0.5 g of the reaction product from the second step, add 0.2 g of polyethylene oxide, 0.15 g of lithium bis(trifluoromethylsulfonyl)imide, and 5 mL of acetonitrile into a sample bottle, stir for 24 h, and apply the resulting uniform solution on a substrate by a doctor blade coating process. Volatilize the solvent to obtain a white film, i.e., a flexible oxide solid electrolyte membrane.

[0042] Step 4: Assemble lithium-ion button cells in the order of positive electrode shell-positive electrode-flexible oxide solid electrolyte-negative electrode-steel sheet-spring-negative electrode shell. The positive electrode of the lithium iron phosphate|lithium full battery is an aluminum foil coated with lithium iron phosphate, and the negative electrode is a lithium sheet; the positive electrode of the lithium symmetric battery is a lithium sheet, and the negative electrode is a lithium sheet.

[0043] Example 4 A room temperature surface modified flexible oxide solid electrolyte raw materials include: 0.5g modified lithium lanthanum zirconium tantalum oxide solid electrolyte, 2.0mL allyltriethoxysilane, 1.0g 2-amino-4-hydroxy-6-methylpyrimidine, 1.32g isocyanoethyl methacrylate, 2.0mL polyethylene glycol monomethyl ether acrylate, 5mg azobisisobutyronitrile, 50mL dimethyl sulfoxide, 20mL cyclohexane, 0.2g polyethylene oxide, 0.2g lithium bistrifluoromethylsulfonyl imide, and 5mL acetonitrile.

[0044] The method for preparing the above-mentioned room-temperature surface-modified flexible oxide solid electrolyte comprises the following steps: Step 1: Weigh 1.0g of 2-amino-4-hydroxy-6-methylpyrimidine into a reaction bottle, add 30mL of anhydrous dimethyl sulfoxide under nitrogen protection, stir at 150°C for 10min, cool to room temperature, then add 1.32g of isocyanoethyl methacrylate, continue stirring and reacting for 2h, after the reaction is completed, precipitate in an ice bath, filter by suction, obtain a filter membrane, wash three times with dimethyl sulfoxide and cyclohexane, dry in a forced air drying oven at 50°C for 12h, and dry in a vacuum oven at 50°C for 12h. A white solid is obtained, namely ethyl 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)methacrylate.

[0045] Step 2: Weigh 0.5 g of modified lithium lanthanum zirconium tantalum oxide solid electrolyte into a reaction bottle, add 2.0 mL of polyethylene glycol monomethyl ether acrylate, 0.5 g of 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidine-2-methyl)(ureido)ethyl methacrylate, 5 mg of azobisisobutyronitrile, and 20 mL of dimethyl sulfoxide. Under nitrogen protection, react at 70°C for 24 hours, cool to room temperature, centrifuge, wash with dimethyl sulfoxide, wash with ethanol three times each, dry in a forced air drying oven at 60°C for 12 hours, and dry in a vacuum oven at 60°C for 12 hours. About 0.5 g of a white solid is obtained.

[0046] Step 3: Weigh 0.5 g of the reaction product of the second step, add 0.2 g of polyethylene oxide, 0.2 g of lithium bis(trifluoromethylsulfonyl)imide, and 5 mL of acetonitrile into a sample bottle, and stir for 24 hours; pour the obtained uniform solution onto a substrate through a doctor blade coating process, evaporate the solvent, and obtain a white film, i.e., a flexible oxide solid electrolyte membrane.

[0047] Step 4: Assemble lithium-ion button cells in the order of positive electrode shell-positive electrode-flexible oxide solid electrolyte-negative electrode-steel sheet-spring-negative electrode shell. The positive electrode of the lithium iron phosphate|lithium full battery is an aluminum foil coated with lithium iron phosphate, and the negative electrode is a lithium sheet; the positive electrode of the lithium symmetric battery is a lithium sheet, and the negative electrode is a lithium sheet.

[0048] Comparative Example 1 The same as Example 4, except that an equal amount of lithium lanthanum zirconium tantalum oxide powder with an average particle size of 4 μm is used instead of the modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

[0049] Performance Testing The room temperature surface modified flexible oxide solid electrolyte membranes prepared in Examples 1 to 4 and Comparative Example 1 were sampled and subjected to the following tests. The test results are shown in Table 1.

[0050] Ionic conductivity test: The AC impedance test was conducted using a Transmission Power 1260A impedance / gain-phase analyzer with a frequency range of 1mHz-0.1Hz. The solid temperature surface modified flexible oxide solid electrolyte membrane was cut into discs with a diameter of 10mm, and carbon-coated aluminum foil was attached on both sides, placed in a mold battery PEEK sleeve, and then stainless steel columns were inserted on both sides to block the electrodes. The test was conducted under a pressure of 360MPa, and the ionic conductivity of the solid temperature surface modified flexible oxide solid electrolyte membrane was calculated.

[0051] Table 1 Performance test project Conductivity (S / cm) Decomposition voltage / V Example 1 <![CDATA[1.43×10 -4 S]]> 4.72 Example 2 <![CDATA[1.25×10 -4 S]]> 4.68 Example 3 <![CDATA[1.62×10 -4 S]]> 4.75 Example 4 <![CDATA[1.80×10 -4 S]]> 4.70 Comparative Example 1 <![CDATA[0.9×10 -4 S]]> 4.41 Analyzing the data in Table 1, we can see that: 1) The room-temperature surface-modified flexible oxide solid electrolytes prepared in Examples 1 to 4 have high electrical conductivity, a wide temperature tolerance range, and high structural stability, and have broad application prospects in the field of polymer composite electrolytes.

[0052] 2) The performance comparison analysis of the room temperature surface modified flexible oxide solid electrolytes prepared in combination with Example 4 and Comparative Example 1 shows that the modified lithium lanthanum zirconium tantalum oxide solid electrolyte can significantly improve the interfacial compatibility and dispersibility of the lithium lanthanum zirconium tantalum oxide powder by grafting the surface of the lithium lanthanum zirconium tantalum oxide powder with allyltriethoxysilane. This improved compatibility helps the lithium lanthanum zirconium tantalum oxide powder to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the flexible oxide solid electrolyte. The modified lithium lanthanum zirconium tantalum oxide solid electrolyte has better structural stability, can maintain good morphology and performance at high temperatures, and is conducive to improving the safety and cycle life of all-solid-state lithium metal batteries. In summary, the modified lithium lanthanum zirconium tantalum oxide solid electrolyte plays a key role in this application. Through the synergistic effect with other raw materials, the comprehensive performance of the flexible oxide solid electrolyte is significantly improved, providing strong support for the development of all-solid-state lithium metal batteries.

[0053] Figure 1 This is a schematic diagram of the scraping process used to prepare the film in Example 1. This process can be used to prepare films of different shapes and sizes according to different requirements.

[0054] Figure 2 The flexible oxide solid electrolyte membrane prepared in Example 1 is composed of Figure 2 It can be seen that the prepared electrolyte membrane has excellent flexibility.

[0055] Figure 3 The conductivity curves of the flexible oxide solid electrolyte membrane prepared in Example 1 and the comparative sample at 30-70°C are as follows: Figure 3 It can be seen that the flexible oxide solid electrolyte membrane has a high ionic conductivity in a wide temperature range and conforms to the Arrhenius equation, indicating that the flexible oxide solid electrolyte membrane has good stability. In summary, the flexible oxide solid electrolyte membrane obtained in Example 1 has good flexibility and conductivity, and can withstand extreme temperatures, and is a solid electrolyte that can be used in flexible conductive devices and lithium metal batteries.

[0056] Figure 4 The capacity and charge-discharge efficiency curves of the flexible oxide solid electrolyte membrane prepared in Example 1 for long-term cycling of a lithium metal full battery at a rate of 0.2C. Figure 4 It can be seen that at a high rate of 0.2, the specific capacity of the whole battery can reach 160mAh / g, and after 500 cycles, it still has a capacity of 130mAh / g.

[0057] Figure 5 The flexible oxide solid electrolyte membrane prepared in Example 1 is used in a lithium ion symmetrical battery at a current density of 0.1 mAh / cm -2Overpotential curve of long cycle, lithium symmetric battery at 0.1mAh / cm -2 The battery was cycled stably for more than 1000 h at a current density of 20 mV with a very small overpotential of 20 mV. The test results show that both the full battery and the symmetrical battery exhibit very good performance.

[0058] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A room temperature surface modified flexible oxide solid electrolyte, characterized in that: The invention comprises the following preparation raw materials: monomer, polyethylene oxide, solvent, initiator, modified oxide ceramic electrolyte and electrolyte salt, wherein the mass of the monomer is 1%-10% of the total mass of each component; the molar ratio of the initiator to the monomer is 0.01%-0.1%; the molar ratio of the electrolyte salt to the monomer is 1:6-12; the mass ratio of the electrolyte salt to the modified oxide ceramic electrolyte is 1:2.5-5; the mass ratio of the polyethylene oxide to the modified oxide ceramic electrolyte is 2:5; and the electrolyte salt is a lithium salt.

2. According to claim 1, a room temperature surface modified flexible oxide solid electrolyte, characterized in that: The lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium perchlorate.

3. According to claim 1, a room temperature surface modified flexible oxide solid electrolyte, characterized in that: The modified oxide ceramic electrolyte is a modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

4. According to claim 3, a room temperature surface modified flexible oxide solid electrolyte, characterized in that: The preparation method of the modified lithium lanthanum zirconium tantalum oxide solid electrolyte is as follows: weigh 0.5 g of lithium lanthanum zirconium tantalum oxide powder with an average particle size of 3-5 μm into a reactor, add 2.0 mL of allyl triethoxysilane, 30 mL of anhydrous ethanol, and 80 μL of deionized water, condense and reflux at 70° C. for 5 hours, centrifuge, wash with water, wash with alcohol three times each, dry in a forced air drying oven at 60° C. for 12 hours, and dry in a vacuum oven at 60° C. for 12 hours to obtain the modified lithium lanthanum zirconium tantalum oxide solid electrolyte.

5. The room temperature surface modified flexible oxide solid electrolyte according to claim 1, characterized in that: The initiator is at least one of azobisisobutyronitrile and potassium persulfate; the solvent is a mixture of one or more of ethanol, N,N-dimethylformamide, dimethyl sulfoxide and acetonitrile.

6. The room temperature surface modified flexible oxide solid electrolyte according to claim 1, characterized in that: The monomer is a mixture of one or more of allyltriethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, vinyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, polyethylene glycol monomethyl ether acrylate, 2-amino-4-hydroxy-6-methylpyrimidine and isocyanoethyl methacrylate.

7. A method for preparing a room temperature surface modified flexible oxide solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: S71, mixing the monomer and the solvent, condensing and refluxing at a certain temperature, filtering, washing, and drying after sufficient reaction, to prepare monomer A; S72, the modified oxide ceramic electrolyte is mixed with the initiator, monomer A, and solvent, reacted under nitrogen protection, cooled to room temperature, centrifuged, washed, and dried to obtain a polymer; and transferred to a glove box for storage; S73. After uniformly mixing the polymer, polyethylene oxide, lithium salt and solvent, the mixture is cast into a polytetrafluoroethylene mold to form a film, and the solvent is evaporated to obtain a room temperature surface-modified flexible oxide solid electrolyte.

8. The method for preparing a room temperature surface modified flexible oxide solid electrolyte according to claim 7, characterized in that: In step S72, the reaction temperature is 60-80°C, and the drying temperature is 50-80°C.

9. An application of a room temperature surface modified flexible oxide solid electrolyte according to any one of claims 1 to 6, characterized in that: The room-temperature surface-modified flexible oxide solid electrolyte is applied to an all-solid-state lithium metal battery. The all-solid-state lithium metal battery is assembled in the order of a positive electrode shell, a positive electrode, a room-temperature surface-modified flexible oxide solid electrolyte, a negative electrode, a steel sheet, a shrapnel, and a negative electrode shell to obtain an all-solid-state lithium metal button battery.

10. The use of a room temperature surface modified flexible oxide solid electrolyte according to claim 9, characterized in that: The positive electrode of the all-solid-state lithium metal battery is a positive electrode coated with one of lithium cobalt oxide, ternary materials, lithium iron phosphate, aluminum foil and lithium sheet, and the negative electrode is a lithium sheet.

Citation Information

Cited By

  • Novel all-solid-state thin film lithium battery and preparation method thereof

    CN120511340A

  • High-ionic-conductivity composite solid electrolyte membrane and preparation method and application thereof

    CN121394526A

  • High-ionic-conducting composite solid electrolyte membrane, and preparation method and application thereof

    CN121394526B